(Mis)Gendering bleeding disorders care: A qualitative case study of a trans person with a bleeding disorder - Fletcher Simon (The Journal of Haemophilia Practice)
The past two decades have seen an evolving discussion as to the complexities of gender identity, particularly with respect to the healthcare needs of transgender (trans) people. The needs of those with a bleeding disorder are relatively unexplored, and there is, therefore, a significant gap in our understanding of how trans people navigate the complexities of living with and accessing care for their bleeding disorder.